Treatments for rotator cuff calcific tendinitis: a systematic review and network meta-analysis of randomized-controlled trials - Yuming Yao; Guang Yang; Shide Jiang; Bingzhou Ji; Hongfu Jin; Peiyuan Tang; Hengzhen Li; Bangbao Lu; Yusheng Li (EFORT Open Reviews)
Purpose: Various conservative and surgical treatments was clinically applied in rotator cuff calcific tendinitis (RCCT), the evaluation of distinction among all available intervention is still lacking. This study aims to systematically compare the efficacy and safety of these interventions and provide guidance for RCCT treatment. Methods: The study utilized four electronic databases for literature retrieval and is registered in PROSPERO. Network meta-analyses (NMA) were conducted for continuous outcomes such as functional improvement and pain relief. For the outcome of calcification deposit resolution, due to discrepancies in statistical methods and insufficient data for pooling, a systematic review was conducted. The Cochrane Risk of Bias 2 tool was used to assess the risk of bias. Results: A total of 33 randomized-controlled trials (RCTs) covering 26 treatment methods were included. In nonsurgical treatments, comprehensive physical therapy (PT) methods (ranked 1st in Surface Under the Cumulative Ranking (SUCRA)) showed the best performance in terms of functional improvement, followed by high-energy extracorporeal shock wave therapy (ESWT-H) + PT, which ranked 2nd. For pain relief, radial shock wave therapy (RSWT) + PT (ranked 1st) was most effective. In surgical treatments, arthroscopic bursectomy debridement of rotator cuff (ABD) + arthroscopic subacromial decompression (ASD) showed similar effects to ABD alone for functional improvement (SMD: −0.01, 95% CI: −0.54 to 0.57) and pain relief (SMD: −0.02, 95% CI: −0.51 to 0.43), with no significant differences observed. For calcification resolution, ultrasound-guided needling (UGN) + subacromial corticosteroid injection (SAI) demonstrated promising therapeutic potential. Conclusion: Comprehensive PT demonstrates superior efficacy in improving functional outcomes, while RSWT + PT significantly alleviates pain. In terms of surgical interventions, ABD alone demonstrated similar clinical effects to ABD + ASD in both functional improvement and pain relief. However, there is currently no direct data to compare the effectiveness of operative versus nonoperative treatments for RCCT. Trial registration: PROSPERO CRD42023476423.